Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1093/ejcts/ezac159
|View full text |Cite
|
Sign up to set email alerts
|

A national analysis of open versus minimally invasive thymectomy for stage I–III thymic carcinoma

Abstract: OBJECTIVES The oncological efficacy of minimally invasive thymectomy for thymic carcinoma is not well characterized. We compared overall survival and short-term outcomes between open and minimally invasive surgical (video-assisted thoracoscopic and robotic) approaches using the National Cancer Database. METHODS Perioperative outcomes and overall survival of patients who underwent open versus minimally invasive thymectomy for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In fact, length of surgery is inconsistently reported throughout the literature and MIS does not always guarantee faster surgical operations. Marulli and colleagues [5] comparing transsternal and robotic thymectomy found a significantly longer surgical time for patients treated with the latter technique, that become non‐significant after a propensity score match; similar results were more recently reported by Hurd [19] in a cohort of patients affected by thymic carcinomas. On the other hand, Casiraghi [14] found a significant longer surgical time in open procedures compared to robotic ones.…”
Section: Commentsupporting
confidence: 68%
“…In fact, length of surgery is inconsistently reported throughout the literature and MIS does not always guarantee faster surgical operations. Marulli and colleagues [5] comparing transsternal and robotic thymectomy found a significantly longer surgical time for patients treated with the latter technique, that become non‐significant after a propensity score match; similar results were more recently reported by Hurd [19] in a cohort of patients affected by thymic carcinomas. On the other hand, Casiraghi [14] found a significant longer surgical time in open procedures compared to robotic ones.…”
Section: Commentsupporting
confidence: 68%
“…Among these 14 patients with thymic carcinoma, 35.7% ( n = 5) were pathologically upstaged. Although MIA for thymectomy has been widely accepted, there is little evidence to support MIA for thymic cancer because MIA is indicated in a minority of patients with thymic carcinoma [ 19 ]. Moreover, the evidence supporting routine LN dissection is also insufficient and controversial, as National Comprehensive Cancer Network guidelines do not mention the indications for LN dissection [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that there were only 22 patients with VATS in this cohort, and that, due to the limitations of the database, some important information such as surgical methods, diagnosis of myasthenia gravis , postoperative complications, and histological classification of thymic cancer, was missing. As well, 54.2% of the study cohort were patients with early-stage malignancies of Masaoka stages I–II, and a very small proportion were of Asian ethnicity [ 11 ]. Recently, Gu et al focused on MIT for the treatment of T2-3NxM0 thymic malignancies, and their data suggested that it could be safely performed in carefully selected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another study used data from the National Cancer Database (NCDB) to compare short-term results and overall survival following open versus minimally invasive thymectomy (MIT) procedures for Masaoka-Koga stage I–III TCs. It is worth noting, however, that only 22 of the patients in that study underwent VATS [ 11 ]. Gu et al explored the impacts of different surgical methods for locally advanced resectable TETs on patient prognoses, including 23 minimally invasive TC and TNET tumors [ 12 ].…”
Section: Introductionmentioning
confidence: 99%